Recovery rate and homogeneity of doping europium into luminescent metal hydrides by chemical analysis1. Issue 13 (14th February 2015) - Hahn, R.; Kunkel, N.; Hein, C.; Kautenburger, R.; Kohlmann, H.
<x xml:space="preserve">Abstract</x> A study on recovery rate and homogeneity of the activator ion concentration in luminescent europium doped metal hydrides and a reliable method for reproducibly doping europium are presented.